PENGARUH PENDIDIKAN KESEHATAN TENTANG DIARE TERHADAP PENGETAHUAN PERILAKU PENCEGAHAN DIARE PADA ANAK USIA SEKOLAH DASAR DI SEKOLAH DASAR 69 MANADO - Gurning, Taruly; Mulyadi, Ns; Rompas, Sefti (Universitas Sam Ratulangi, 2014)
Abstrack: Introduction School Children are children aged 6 - 12 years, school children are susceptible to the disease one of which is a diarrheal disease. Diarrhea is a bowel disorder characterized by bowel movements more than 3 times a day with liquid stool consistency, can be accompanied by mucus and even blood. The purpose of the study Increasing knowledge of the behavior of the prevention of diarrhea in children through school health education. The research method of this study Pre experimental design of this study to design one group pretest and post test design. Respondents in this study were fifth grade school age children up to 30 children, with total sampling, conducted pre-test questionnaire mengisis, then performed through the medium of health education leaflets, after the post-test was conducted to fill the questionnaire. test analysis using a non-parametric test using the Wilcoxon test to determine the effect of health education on the knowledge of the behavior of the prevention of diarrhea in children of school age. Results of the study P = 0.001 indicates that there is a significant difference regarding knowledge of diarrhea before and after health education. Conclusion research ie no effect of health education on the knowledge of the behavior of diarrhea prevention of diarrhea in children aged Primary School Public Elementary School 69 in Manado. Suggestion health education is more often carried out by the school in order to add insight to children - primary school children and attempt an understanding of the behavior of disease prevention, especially diarrhea. Keyword : Diarrhea, knowledge, health education, school-age children Abstrak: Pendahuluan Diare adalah gangguan buang air besar atau BAB yang ditandai dengan buang air besar lebih dari 3 kali sehari dengan konsistensi tinjak cair, dapat disertai lendir bahkan darah. Tujuan penelitian meningkatkan pengetahuan perilaku pencegahan diare pada anak sekolah melalui pendidikan kesehatan. Metode penelitian Pre eksperimental dengan rancangan one group pretest and post test design. Responden anak usia sekolah kelas V sebanyak 30 anak dengan menggunakan Total Sampling, dilakukan pre test mengisis kuesioner dilakukan pendidikan kesehatan melalui leaflet, setelah itu dilakukakan post test mengisi kuesioner. Uji analisis menggunakan uji non parametrik menggunkan Wilcoxon Test untuk mengetahuai pengaruh pendidikan kesehatan terhadap pengetahuan perilaku pencegahan diare pada anak usia sekolah. Hasil penelitian P = 0,001 terdapat perbedaan bermakna mengenai pengetahuan tentang diare sebelum dan sesudah dilakukan pendidikan kesehatan. Kesimpulan penelitian ada pengaruh pendidikan kesehatan tentang diare terhadap pengetahuan perilaku pencegahan diare pada anak usia Sekolah Dasar di SD Negeri 69 Manado. Saran pendidikan tentang kesehatan lebih sering dilaksanakan oleh sekolah agar dapat menambah wawasan bagi anak – anak sekolah dasar dan upaya pemahaman tentang pencegahan tentang penyakit terutama diare. Kata Kunci : Diare, Pengetahuan, Pendidikan Kesehatan,Usia Sekolah